2017
DOI: 10.1177/1463949117747108
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering cultural assumptions: Using a critical incident technique during an international student-teaching field experience

Abstract: This research examined the critical incidents of 10 United States (US) early childhood student teachers during a three-week university-sponsored international field experience conducted in three urban preschools in Kathmandu, Nepal. The purpose of employing the critical incident technique was to allow the US student teachers to reflect critically on successful and unsuccessful intercultural interactions in an effort to identify cultural assumptions about teaching young children. The approach was used not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This method is an active process described by Tripp (1994) in opposition to a more traditional biography method because it aims to enable individuals to “break with the past” (p. 69) and “meet specific practical concerns” (p. 74). This reflective framework, according to Madrid Akpovo (2019), allows teachers to “make cognitive and behavioral changes based on what is learned” to that end the focus is on the process of self-reflection and the fact that it is directly connected to future action steps (p. 148). This study builds on prior research on self-reflection and intercultural awareness by investigating the efficacy of providing participants with a particular self-reflective tool and investigating if it does, in fact, inspire a desire to modify behaviors in the future (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is an active process described by Tripp (1994) in opposition to a more traditional biography method because it aims to enable individuals to “break with the past” (p. 69) and “meet specific practical concerns” (p. 74). This reflective framework, according to Madrid Akpovo (2019), allows teachers to “make cognitive and behavioral changes based on what is learned” to that end the focus is on the process of self-reflection and the fact that it is directly connected to future action steps (p. 148). This study builds on prior research on self-reflection and intercultural awareness by investigating the efficacy of providing participants with a particular self-reflective tool and investigating if it does, in fact, inspire a desire to modify behaviors in the future (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Critical incident analysis is a structured critical reflection method and has been defined by Tripp (1994) as the study of self-identified significant or commonplace moments in a practitioner’s life both to “recall, document, and explain past events…as a way of illuminating, articulating, understanding, and gaining control over our current professional practice and habits” (p. 69). Unlike a more traditional biography method, the critical incident analysis is more intentionally aimed at improving practice through the process of examining “judgments that are attached to seeing classroom events and practices” (Madrid Akpovo, 2019). This inquiry-based method has been used in several fields including teaching, medicine, counseling and social work to analyze and work to improve the practice of both in-service and preservice professionals.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Consistent with Akpovo' s (2019) perspective, we believed having candidates choose the incident, instead of the instructors, and prompting them to explain the significance of the incident could identify candidates' perspectives of why the incident was instructive to them. Akpovo (2019) suggests that "it is not the event itself that is important; it is how the teacher interprets the event, and the resulting actions and reactions based on these insights." p.148).…”
Section: Data Sources and Collectionmentioning
confidence: 99%
“…those with a teacher education degree or license) educators enrolled in university-sponsored international programs. Samara, a White female academic from the USA, has spent the past seven years conducting research with US pre-service early childhood teachers at urban preschools located in Kathmandu, Nepal (Madrid, Baldwin, & Belbase, 2016; Madrid Akpovo, 2017; Madrid Akpovo, Moran, & Brookshire, 2018). Lydiah, an academic originally from Kenya who now resides in the USA, has taken both pre-service and in-service teachers to Kenya for the past 14 years (Kambutu & Nganga, 2008; Nganga, 2016; Nganga & Kambutu, 2017).…”
Section: Preparing Intercultural Professionalsmentioning
confidence: 99%
“…Contextually appropriate practice (Li and Chen, 2016), as well as the notion that teaching is a cultural activity, should be ongoing aspects of the reflective process, as pre-service and in-service teachers revisit and uncover their cultural assumptions. This revisiting and uncovering of cultural assumptions can lead to increased understandings about ethnocentrisms regarding quality education in various cultural contexts (Madrid Akpovo, 2017; Kroll and Meier, 2015; Tobin, 2005; Tobin et al, 1989, 2009).…”
Section: We Cannot Assume That Change Will Occur: the Problem Of The mentioning
confidence: 99%